The Effect of Earning Per Share (EPS) and Dividend Per Share (DPS) on Share Prices - Deni Sunaryo (Kusuma Negara Business School, 2020)
The purpose of this research was analyzing the effect of Earnings per Share (EPS) and Dividend Per Share (DPS) on Stock Price because of the gap in previous studies. The population in this study were 19 automotive and spare parts industrial companies listed on the Southeast Asian Stock Exchange for the 2014-2018 period. The method used is purposive sampling so that 11 companies that present complete financial reports according to the variables studied and obtained as many as 55 company samples. The analysis techniques used are multiple linear regression analysis, partial test (t test), simultaneous test (F test). The results showed that partially EPS had a significant effect on stock prices while DPS had no significant effect on stock prices. But simultaneously EPS and DPS have a significant influence on the stock prices of the automotive and spare parts subsector companies in Southeast Asia. The company should be able to manage your income properly. For further research can expand the variables and dimensions, examine with the observation period of data is long and the latest as well as using testing methods different stats so that can give research results a more accurate and different.